The place of agricultural issues in the Sandomierz press (1829–2022) - Mikosz, Joanna (Zeszyty Wiejskie (Online), 2023)
The purpose of the article is to present the periodicals that discussed issues of cultivation, fruit farming, horticulture and animal breeding in Sandomierz. The time frame covers newspapers published between 1829–2022. The article consists of two parts. The first provides the titles of periodicals published in Sandomierz between 1829–1939, which addressed topics related to agriculture or livestock farming. The second part presents periodicals covering this subject matter that were printed in Sandomierz from 1945–2022. The author indicates that issues related to agriculture in Sandomierz and in the region were not only reflected in the local press published after the political transformation, but became the subject of scholarly and popular-scientific reflection.